The growing potential of the men’s grooming segment in Austria - Seyler, Patrizia (2017)
Men’s grooming has become an attractive and lucrative, yet challenging market within the personal care industry. Given men’s ever more sophisticated grooming routine, companies are faced with the necessity of adjusting to local adaptations and trends. The current study therefore chose to focus on an analysis of men’s grooming habits and routines in Austria. The findings suggest that companies should focus on the skin care sector, as it offers a variety of growth opportunities. Furthermore, the male consumer decision journey has developed into a complex cycle. Therefore, implementing targeted marketing activities and providing information for decision-making to trigger needs are essential to capture the consumer.